(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article is dedicated to Marina Tsvetaeva and her inexhaustible poetry in Russian and world literature, she is like a Russian poetess, proseand translator, of which she isone of the largest representatives and poets of the Silver Age of Russian literature. The poem "Homesickness" is analyzed!